Reduced efficacy of single-dose albendazole against Ascaris lumbricoides, and Trichuris trichiura, and high reinfection rate after cure among school children in southern Ethiopia: a prospective cohort study - Tigist Dires Gebreyesus; Eyasu Makonnen; Tafesse Tadele; Kalkidan Mekete; Habtamu Gashaw; Heran Gerba; Eleni Aklillu (BMC, 2024)
Abstract Background Mass drug administration (MDA) program of albendazole to at-risk populations as preventive chemotherapy is the core public health intervention to control soil-transmitted helminths (STHs). Achieving this goal relies on drug effectiveness in reducing the parasite reservoirs in the community and preventing reinfection. We assessed the efficacy of albendazole against STH parasite infection and reinfection status after cure. Methods A total of 984 schoolchildren infected with at least one type of STH parasite (hookworm, Ascaris lumbricoides, Trichuris trichiura) in southern Ethiopia were enrolled and received albendazole and praziquantel in MDA campaign conducted from January to March 2019. Stool exams at week-4 and at week-8 of post-MDA were done using Kato Katz technique. The primary outcome was efficacy assessed by cure rate (CR) and fecal egg reduction rates (ERRs) at four weeks of post-MDA. The secondary outcome was reinfection status defined as parasite egg positivity at eight weeks among those who were cured at 4 weeks of post-MDA. Group comparisons in CR and related factors were assessed with chi-square or Fisher's exact tests. Predictors of CR were examined through univariate and multivariate regression analyses. Results The overall CR and ERR for hookworm infection were 97.2% (95% CI 94.6-99.4) and 97.02%, respectively. The overall CR and ERR for A. lumbricoides were 71.5% (95% CI 68.3-74.6) and 84.5% respectively. The overall CR and ERR and for T. trichiura were 49.5% (95% CI 44.8-54.2) and 68.3%, respectively. The CR among moderate T. trichiura infection intensity was 28.6%. Among children cured of hookworm, A. lumbricoides and T. trichiura at week 4 post-MDA, 4.6%, 18.3% and 52.4% became reinfected at week-8 post-MDA, respectively. Significantly lower CR (36.6%) and higher reinfection after cure (60.6%) among A. lumbricoides and T. trichiura coinfected children than A. lumbricoides only (CR = 69.6%, reinfection rate = 15.1%) or T. trichiura only infected children (CR = 55.6%, reinfection rate = 47.1%) was observed. Pre-treatment coinfection with ≥ two types of STH parasites was significantly associated with re-infection after cure. Conclusion Albendazole MDA is efficacious against hookworm but has reduced efficacy against A. lumbricoides and is not effective against T. trichiura. The low drug efficacy and high reinfection rate after cure underscore the need for alternative treatment and integration of other preventive measures to achieve the target of eliminating STHs as a public health problem by 2030. Graphical Abstract